KETERAMPILAN SOSIAL SISWA DALAM PEMBELAJARAN IPA FISIKA MELALUI PENERAPAN STRATEGI WHOLE BRAIN TEACHING DI KELAS VII SMPN 29 PEKANBARU - Putri, Ananda; Azizahwati, Azizahwati; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to describe the social skills in class VII SMP 29 Pekanbaru through the implementation of Whole Brain Teaching strategy. The expected benefits of this research for the basis of further determine the success of students using many different learning approaches. This study was conducted in SMP 29 Pekanbaru in November 2015. The subjects were students VII6 totaling 42 students. The form of this research are used pre-experimental design form the One Shot Case Study. Data collection tools in this study was the social skills observation sheet. The results were obtained based on the indicators of social skills, they are; to encourage participation; taking turns and sharing of tasks; active listening, students have the social skills that are still categorized each meeting with the average percentage of each indicator to increase as high. It is possible with a whole brain teaching strategies can practice social skills class VII SMP 29 Pekanbaru on substances that change the subject and closed it.Key Words: Social Skills Student, Whole Brain Teaching, Descriptive Analysis